Prototype Alat Pendeteksi Kebocoran Gas LPG Berbasis IOT - Soesilo, Eddy; Fayuza, Isriwan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The role of LPG (Liquefied Petroleum Gas) at this time is very important for human life both in households and in industry. Since the existence of the energy conversion program from petrol to LPG gas, new problems have arisen. Around the beginning of January to July 2010, incidents of explosions of LPG gas tube which claimed cause casualties, and this was confirmed by the widespread coverage in the mass media, especially television. The explosion of an LPG gas tube usually occurs in a three-kilogram gas tube. Leakage of LPG tube or equipment is still one of the main causes of explosions in LPG gas tube, which results from the absence of visible gas leaks. The gas explosion occurs when the LPG gas cannot be recognized by the owner, the position of the gas that is not in accordance with the standard use of the gas can result in a very fatal explosion and cause casualties. Of the many cases circulating in society and industry, it is necessary to treat this type of fuel specifically. Therefore, there is a need for an early warning system for LPG gas and its devices in order to deal with gas leaks which can result in fatalities. This system is designed using the MQ-5 sensor and NodeMCU as the main controller that can connect to the internet. Later this tool is expected to be able to provide early warning in the form of notifications on smartphones to users in the event of a leak in a gas cylinder.